Factors contributing to paracetamol overdoses (intentional and accidental) amongst adult and paediatric populations in the United Kingdom: protocol for a systematic review and meta-analysis - Andrew Radley; Nasloon Ali; Heather Cassie; Giorgia De Paoli (BMJ Open)
Introduction Paracetamol, the most used analgesic medicine in the world, is considered a safe treatment, but when overdosed, it can be fatal. Evidence suggests that despite sales legislations, paracetamol overdose still accounts for around 100 000 accident and emergency visits and 50 000 hospital admissions per year in the UK. This systematic review aims to describe the possible factors linked to paracetamol overdoses (intentional and/or accidental) in the adult and child populations in the UK and the subgroups of the population that are at higher risk and identify any preventative interventions.Methods and analysis This review will be carried out in accordance with the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) guidance. Literature searches will be performed using six bibliographic databases: MEDLINE via PubMed, EMBASE, SCOPUS, PsycINFO, the Cochrane Library and PROSPERO register. Grey literature and social media will also be searched, and article reference lists are reviewed. Studies included will be in English with populations in the UK from 1998 onwards, experiencing paracetamol overdose (intentional or accidental), with no age restriction. Title and abstract screening and full-text review of included articles will be performed by two independent reviewers (with a third member to resolve disagreement). The risk of bias will be assessed using the JBI critical appraisal checklist. The quality of any systematic reviews included will be assessed using the AMSTAR 2 tool or the Mixed Methods Appraisal Tool (MMAT), as appropriate. It is anticipated to adopt a narrative synthesis of the findings via a thematic analysis. Meta-analysis and subgroup analysis will be considered if data are available.Ethics and dissemination Ethics approval is not required for this work since no data will be collected. Results will be disseminated through a peer-reviewed publication and local as well as national conference presentations; and a range of creative and inclusive methods and formats to inform and educate patients and the community.PROSPERO registration number CRD42024555406.